2021
DOI: 10.1038/s41523-021-00288-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot of an online, personalized risk assessment tool for a breast cancer precision medicine trial

Abstract: Breast cancer risk reduction has been validated by large-scale clinical trials, but uptake remains low. A risk communication tool could provide personalized risk-reduction information for high-risk women. A low-literacy-friendly, visual, and personalized tool was designed as part of the Women Informed to Screen Depending On Measures of risk (WISDOM) study. The tool integrates genetic, polygenic, and lifestyle factors, and quantifies the risk-reduction from undertaking medication and lifestyle interventions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The study was not randomised and was dramatically impacted by the COVID-19 pandemic with uptake of the study and of risk appointments in those identified at moderate or high risk almost certainly affected. As such, generalisability of the results may need to be reassessed after the results from two large randomised trials [ 32 , 33 ] are available. We were unable to use the original counterbalanced design, which would have allowed better estimation of differences between BC-Predict and NHSBSP rates and could not answer the question of whether there were lower rates for screening uptake (although there was no evidence of this in PROCAS-1 [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was not randomised and was dramatically impacted by the COVID-19 pandemic with uptake of the study and of risk appointments in those identified at moderate or high risk almost certainly affected. As such, generalisability of the results may need to be reassessed after the results from two large randomised trials [ 32 , 33 ] are available. We were unable to use the original counterbalanced design, which would have allowed better estimation of differences between BC-Predict and NHSBSP rates and could not answer the question of whether there were lower rates for screening uptake (although there was no evidence of this in PROCAS-1 [ 10 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It also addresses a number of research gaps identified in breast cancer risk stratification [ 23 , 34 ]. There are a number of other important initiatives in progress including the WISDOM [ 32 ] and MyPEBS [ 33 ] studies, but both are still open to recruitment and have not yet reported results of risk feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Personal risk of breast cancer is a difficult concept to grasp. Breast cancer risk prediction tools are mainly designed for providers, hence the participant may have a limited understanding of the results [ 52 ]. We deliberated over the readiness of the Singapore’s population to receive personalised disease risk results with various stakeholders (representatives of the hospitals and clinics, ethics representatives, public health experts, and researchers), and concluded that only the general risk classification (below-average, average and above-average risk) is to be conveyed to the participants as part of this research study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efficacy of risk-reducing medication, clinician recommendation and patient uptake are both dismal, although both vary greatly depending on the clinical scenario (24). Recently, efforts have been made to improve risk prediction to increase the uptake of prophylactic endocrine therapy in women at increased risk (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%